Pertautan Toleransi Agama dan Sikap Apologetis: Tegangan antara Konfrontasi dan Konfirmasi Kebenaran Kristen di Tengah Pluralitas Agama - Romelus Blegur (Program Pascasarjana UKIM, 2023)
The focus of this research is to link religious tolerance and apologetic attitude as two important poles for religious followers even though both of them stand in tension between confrontation and confirmation. By opening this space, access to convey Christian beliefs in the midst of religious diversity becomes more free and flexible. The result of this research is that the link between tolerance and apologetic attitude can be made possible by maintaining similarity, being open and respecting the intrinsic values of other religious beliefs. By doing this to fellow believers of other religions, Christianity will also receive the same respect in return.